DEVELOPMENT OF GEOMATHFUN INTERACTIVE LEARNING MEDIA ON SOLID GEOMETRY - Jusra, Hella; Suprapto, Annisa Maghfyracaesar (International Research-Based Education Journal, 2022)
This study aims to determine the feasibility of the product of a developed geomathfun learning media. This research uses R&D (Research and development) research methods, with a 4D development model, in which there are four stages, namely definition, design, development and dissemination. The data was obtained using the results of questionnaires and observations. The research sample is the fifth-grade students of SDN Pesanggrahan 10 Pagi. And get the results of media validation of 81% with a very decent category while material validation gets a percentage of 80% with a decent category. In this way, the geomathfun learning media contributes well to learning mathematics in spatial building materials.